Safe and flexible ion gel based composite electrolyte for lithium batteries. Issue 37 (9th September 2016) - Que, Mingming; Tong, Yongfen; Wei, Guochang; Yuan, Kai; Wei, Junchao; Jiang, Yaoquan; Zhu, Hui; Chen, Yiwang
Abstract : Safe and flexible electrolyte functioning well at wide temperature range and deformable conditions by incorporating ion gel in electrospun membranes. Abstract : A new family of three-arm polymer ionic liquids (PILs) with X counter anions [3P(MPBIm-X), X − = Br −, CF3 SO3 − (Tf − ) and (CF3 SO3 )2 N − (TFSI − )] were successfully synthesized. The effects of anion type on the chemical, thermal and ionic conductivity of PILs have been investigated. Results showed that 3P(MPBIm-X) with TFSI − counter anion (3P(MPBIm-TFSI)) possessed better thermal property and ionic conductivity. Furthermore, to obtain safe and flexible electrolytes with superior performance, solid-like composite electrolyte (SLCE) was fabricated by filling ion gel, the mixture of 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (EMIM-TFSI) incorporated into 3P(MPBIm-TFSI), in the micropores of PVDF-HFP electrospun membranes. It was found to be thermally stable up to 370 °C and electrochemically stable above 4.8 V. SLCE was nonflammable and showed negligible leakage property when subjected to load. At 50 °C, ionic conductivity of SLCE could reach 1 mS cm −1 (1.2 × 10 −3 S cm −1 ), which is approximately two orders of magnitude higher than that of 3P(MPBIm-TFSI). Moreover, Li/SLCE/LiFePO4 solid-like state cells exhibited excellent reversible charge/discharge reactions and considerable capacity retention up to medium rates. Coulombic efficiency can remain 100% even after 100 cycles. Potential application of SLCE as an electrolyte for flexible lithium batteries was explored by scrutinizing the electrochemical performance of cells. Consequently, pouch cell exhibited stable cycling performance even in wrinkled configurations, without suffering from internal short-circuit failures between electrodes.